INTERVENSI KEPERAWATAN PADA PENDERITA GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS: SYSTEMATIC REVIEW: Nursing Intervention for Patients With Chronic Renal Failure Who Undergoing Hemodialysis : A Systemtic Review - Hayyu Sitoresmi; Andi Masyitha Irwan; Elly Lilianty Sjattar (LPPM STIKES Pemkab Jombang, 2020)
Background : Nursing intervention is very important for care providers to achieve adequacy in hemodialysis (HD) process. Nurses as the front line in services need to know precisely the nursing interventions that can reduce the mortality rate of HD patients. Objective: to identify what kind of nursing interventions can be done during hemodialysis. Methods: Pubmed, Science Direct, Wiley Online, Proquest, and Google Scholar are databases used in collecting articles with relevant keywords and PRISMA guidelines. Results: obtained six randomized controlled trial articles according to the inclusion criteria. The research article presents nursing interventions such as inhalation therapy, training programs, foot massage, acupressure, cold dialysate use, and music therapy. The intervention can reduce complications that often occur in HD patients and have appropriate duration to be applied during intradialytic phase. Conclusion: nursing intervention can be witnessed to overcome complaints of nausea, vomiting, pain, pruritus, physical weakness, cramps, and psychological disorders. But it needs to be adjusted to the patient's condition and coordination with other medical officers in improving the quality of nursing care.